ANALISIS PENGEMBALIAN KREDIT UNGGULAN (KUPEDES) PADA PT. BRI TBK UNIT MIKRO CABANG BENGKALIS - Dwi Yudi Pranata; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of research is to knowing the loans repayments featured (KUPEDES) PT.BRI, Tbk Micro Branch Unit Bengkalis. KUPEDES is featured credit company-owned rureal banks PT.BRI, Tbk Micro Branch Unit Bengkalis.The repayment is based on the level of collectibility, repayment credits can be measured by the five dimensions (5), namely performing loans, loans in which particular attention, substandard loans, doubtful loans and bad loans. In this research population is KUPEDES customer PT.BRI, Tbk Micro Branch Unit Bengkalis. Sampling technique is accidental sampling and get 100 respondens. Result of the research is conclueded that the loan repayment KUPEDES is low category.Keyword: repayment on loans, KUPEDES, banking